Dynamics of psychophysical health profile of female medical university students - Avdeeva M.S.; Strelnikova I.V.; Maltsev D.N.; Kononets V.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to study the dynamics of the psychophysical health profile: physical development, physical fitness, self-esteem of health and addictive behavior of first- and final-year medical university students. Methods and structure of the study. We examined the dynamics of physical development and physical fitness of 147 first- and final-year students of a medical university. The respondents took part in psychological testing: the «self-assessment of health» test (SH according to V.P. Voitenko) and the «diagnostics of addictive behavior» test (according to N.N. Telepova). Results and conclusions. It is shown that the anthropometric indicators of the subjects do not change during the training period. At the same time, the indicators of strength and speed-strength abilities decrease. Self-assessment of health among freshmen and graduates remains approximately at the same level. However, graduate students develop the prerequisites for addictive behavior. Thus, the study showed the presence of negative changes in physical fitness and the formation of addictive behavior among senior female students. At the same time, the level of self-assessment of health status did not change throughout the entire period of study.